A novel PNIPAM-Modified polyurethane/carboxymethyl cellulose photo-thermoresponsive hydrogel loaded with gemcitabine to suppress esophageal cancer cells via VEGF-mediated angiogenic pathway inhibition - Shirong Wu; Huachuan Zhang; Yu Zhang; Ya Zhao; Mengqi Xiang; Liqiong Hao; Jing Chen (Journal of Biological Engineering)
Abstract This study reports the development of a thermoresponsive hydrogel composed of poly(N-isopropylacrylamide)-modified polyurethane (PNIPAM-PU) and carboxymethyl cellulose (CMC) for the controlled delivery of gemcitabine (GEM) in esophageal cancer treatment. Characterization by XRD and FTIR confirmed successful synthesis and structural integrity. The drug loading capacities were 76.2 ± 2.5% for PNIPAM-PU/CMC@GEM and 83.4 ± 3.4% for PNIPAM-PU/CMC@GEM + NIR. SEM analysis revealed pore diameters of 46.96 ± 12.94 μm (PU/CMC) and 42.96 ± 13.49 μm (PNIPAM-PU/CMC@GEM). Rheological analysis showed a sharp sol–gel transition at 37 °C. Drug release reached 25% over 24 h without NIR, increasing to 75% with NIR exposure. In vitro MTT assay showed significant cytotoxicity in KYSE-140 cells, with IC₅₀ values of 52.85 ± 2.5, 90.97 ± 3.6, 60.76 ± 2.8 and 41.59 ± 2.4 µg/mL for GEM, PU/CMC, PNIPAM-PU/CMC@GEM, and PNIPAM-PU/CMC@GEM + NIR, respectively. Biocompatibility assessment using the normal human esophageal epithelial cell line Het-1 A demonstrated increased cell viability (85%) without showing any morphological changes when treated with fabricated hydrogel formulations, confirming the non-toxic nature of the carrier system. Further, JC-1 and AO-EB staining confirmed mitochondrial depolarization and apoptosis of KYSE-140 cells after exposed to PNIPAM-PU/CMC@GEM + NIR. In vivo studies demonstrated tumor inhibition rates of 48.72%, 10.26%, 61.54%, and 74.36% for GEM, PU/CMC, PNIPAM-PU/CMC@GEM, and PNIPAM-PU/CMC@GEM + NIR, respectively, with minimal side effects. qRT-PCR and Western blot analysis showed VEGF downregulation and angiogenesis inhibition. These findings support the potential of PNIPAM-PU/CMC@GEM hydrogel as an effective localized therapy for esophageal squamous cell carcinoma (ESCC).